2019
DOI: 10.1177/1753944719851950
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, depression and cardiovascular disease in women: the role of the immune system across critical reproductive events

Abstract: Women are at increased risk for developing depression and cardiovascular disease (CVD) across the lifespan and their comorbidity is associated with adverse outcomes that contribute significantly to rates of morbidity and mortality in women worldwide. Immunesystem activity has been implicated in the etiology of both depression and CVD, but it is unclear how inflammation contributes to sex differences in this comorbidity. This narrative review provides an updated synthesis of research examining the association o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 237 publications
(246 reference statements)
0
66
0
7
Order By: Relevance
“…In ammation (58) and oxidative stress (34) have been implicated in the etiology of depression and disturbed sleep (59); in turn, OC use has been associated with depression (60). More longitudinal research is needed to improve the understanding of mechanisms induced by in ammation in OC-users possibly affecting the psyconeurological pathways (61).…”
Section: C-reactive Proteinmentioning
confidence: 99%
“…In ammation (58) and oxidative stress (34) have been implicated in the etiology of depression and disturbed sleep (59); in turn, OC use has been associated with depression (60). More longitudinal research is needed to improve the understanding of mechanisms induced by in ammation in OC-users possibly affecting the psyconeurological pathways (61).…”
Section: C-reactive Proteinmentioning
confidence: 99%
“…Recently, studies have shown that the pathogenesis of hippocampal lesions and neuronal cell death in patients with depression might be related to the explosive activation of inflammatory reactions [1]. The "cytokine theory" suggests that stress-stimulated or over-activated immune systems produce inflammatory cytokines and play an important role in the pathogenesis of depression [2], which have been confirmed by clinical trials [3][4][5] and animal experiments [6,7]. Therefore, anti-inflammatory treatment for reducing the hippocampal inflammatory response and improving hippocampal function have become a new target for the prevention and treatment of depression.…”
Section: Introductionmentioning
confidence: 96%
“…Of note, the link between inflammation and kidney fibrosis has been well established and the pharmacological suppression of inflammation slows down renal dysfunction with a reduction in glomerulosclerosis and interstitial fibrosis (Beer, Mayer, & Kronbichler, ; Braun et al, ; Eardley et al, ). The disparity in inflammatory markers between genders is also established and mainly attributed to sex hormones and other gender‐biased factors such as body composition, physical/sexual maturation, and behavioral changes during adolescence (Mattina, Lieshout, & Steiner, ; Shanahan et al, ). The risk of chronic inflammation and the associated diseases is inversely proportional to aging during which sex hormones in both genders significantly decrease but to a different extent (Laaksonen et al, ; Mattina et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The disparity in inflammatory markers between genders is also established and mainly attributed to sex hormones and other gender‐biased factors such as body composition, physical/sexual maturation, and behavioral changes during adolescence (Mattina, Lieshout, & Steiner, ; Shanahan et al, ). The risk of chronic inflammation and the associated diseases is inversely proportional to aging during which sex hormones in both genders significantly decrease but to a different extent (Laaksonen et al, ; Mattina et al, ). Women smokers are now known to be at higher risk of developing dyslipidemia, cardiovascular diseases, and lung diseases (Hsu et al, ; Lee et al, ; Peters, Huxley, & Woodward, ; Yahagi, Davis, Arbustini, & Virmani, ).…”
Section: Introductionmentioning
confidence: 99%